Analyzing the Impact of Refactoring on Bad Smells - Tavares, Cleiton; Bigonha, Mariza; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Refactoring aims to remove bad smells and increase software maintainability by improving the software structure without changing its behavior. However, some studies show that refactoring tools may introduce new bad smells into the source code, but to the best of our knowledge, we have not been able to find a complete catalog that states the bad smells introduced from refactoring. To bridge this gap, this paper goal is to evaluate the impacts of refactoring on the detection of bad smells in open-source Java systems. Hence, we want to know if and when the automated refactoring removes or introduces bad smells.